KEBIJAKAN FORMULASI HUKUM PIDANA TERHADAP “JUSTICE COLLABORATOR” DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Oly Viana Agustine, Eko Soponyono, Pujiyono (Diponegoro Law Journal, 2012)
Policies in making a good criminal law essentially inseparable from crime prevention efforts. Corruption is the behavior of public officials who illegally enrich themselves or  others,  the  abuse  of  public  power.  Need  to  break  the  law  to  accelerate  the eradication of corruption is to play the role of justice collaborator. But positive law, not to encourage people to take part as a justice collaborator